The Palgrave Encyclopedia of Victorian Women's Writing - Scholl, Lesa.; Morris, Emily (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
Since the late twentieth century, there has been a strategic campaign to recover the impact of Victorian women writers in the field of English literature. However, with the increased understanding of the importance of interdisciplinarity in the twenty-first century, there is a need to extend this campaign beyond literary studies in order to recognise the role of women writers across the nineteenth century, a time that was intrinsically interdisciplinary in approach to scholarly writing and public intellectual engagement. .
1. Reform -- 2. Novels -- 3. Health/Wellness -- 4. Religion -- 5. Economics -- 6. Journalism -- 7. New Woman -- 8. Travel Writing -- 9. Poetry -- 10. Literary Criticism -- 11. Domestic Management -- 12. Food Studies -- 13. Short Stories -- 14. Sexuality -- 15. Philosophy -- 16. Science -- 17. Life Writing -- 17. Fashion -- 18. Children's Writing -- 19. Commonwealth -- 20. Art History/Art Criticism -- 21. Theatre/Playwrights -- 22. Education -- 23. Translators -- 24. Music -- 25. Suffrage -- 26. Engineering -- 27. Lesbian/Queer Writers -- 28. Anthropology/Archaeology -- 29. History.
Keywords: Literature, Modern-19th century; Literature-History and criticism; History, Modern; Nineteenth-Century Literature; Literary History; Modern History